2011
DOI: 10.1002/casp.1129
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs Contributing to HIV‐related Stigma in African and Afro‐Caribbean Communities in the Netherlands

Abstract: Thirty years after the first diagnosis, people living with HIV (PLWH) around the world continue to report stigmatizing experiences. In this study, beliefs contributing to HIV-related stigma in African and Afro-Caribbean diaspora communities and their cultural context were explored through semistructured interviews with HIV-positive (N = 42) and HIV-negative (N = 52) African, Antillean and Surinamese diaspora community members in the Netherlands. Beliefs that HIV is highly contagious, that HIV is a very severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…Stigma was similarly fuelled by perceptions of strict confidentiality rendering HIV invisible within the community, the reluctance of affected individuals and family to speak out and engage the community, the reluctance of the community to discuss its role in perpetuating silence, and cultural, historical and social norms that associated HIV with moral culpability, death and disease. Stutterheim and colleagues [ 48 ] found HIV stigmatising beliefs were strengthened and prolonged by “silence, denial and [cultural] taboo” (pp. 478) prohibiting talk about sex and HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Stigma was similarly fuelled by perceptions of strict confidentiality rendering HIV invisible within the community, the reluctance of affected individuals and family to speak out and engage the community, the reluctance of the community to discuss its role in perpetuating silence, and cultural, historical and social norms that associated HIV with moral culpability, death and disease. Stutterheim and colleagues [ 48 ] found HIV stigmatising beliefs were strengthened and prolonged by “silence, denial and [cultural] taboo” (pp. 478) prohibiting talk about sex and HIV.…”
Section: Discussionmentioning
confidence: 99%
“…In the Western world, HIV is a chronic medical condition that nonetheless remains stigmatized as a result of its association with behaviors often considered to be norm-violating, such as sex between men, having multiple sex partners, commercial sex work, and intravenous drug use (Stutterheim, Bos, van Kesteren, et al, 2012). HIV is also often construed as contagious and severe, and those who have HIV are frequently considered personally responsible for having acquired HIV (Stutterheim, Bos, van Kesteren, et al, 2012). A large body of research has demonstrated that disclosure of HIV status can lead to stigma that subsequently has substantial costs for psychological, social, and physical well-being Stutterheim, Bos, van Kesteren, et al, 2012;Stutterheim et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, people living with HIV (PLWH) are often associated with behaviors that are perceived by some to violate social norms, such as commercial sex work, homosexuality, and intravenous drug use. [7][8][9] Combined, these perceptions contribute to PLWH feeling stigmatized, and, indeed, negative reactions to PLWH have been found to occur across a broad range of settings. [10][11][12][13] One such setting is health care.…”
mentioning
confidence: 99%